2014
DOI: 10.1590/1981-6723.1614
|View full text |Cite
|
Sign up to set email alerts
|

Efeito das informações e características da embalagem na expectativa e aceitação de café solúvel adicionado de café torrado micronizado

Abstract: Efeito das informações e características da embalagem na expectativa e aceitação de café solúvel adicionado de café torrado micronizado Impact of the information and package characteristics on the expectation and acceptance of a soluble coffee with added micronized roasted coffee Campinas, v. 17, n. 3, p. 243-251, jul./set. 2014 DOI: http://dx.doi.org/10.1590/1981-6723.1614 Efeito das informações e características da embalagem na expectativa e aceitação de café solúvel torrado micronizado FRANCISCO, J. S. et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…CB and IC packaging were also equally accepted (Table 2); the high average acceptance (mean value of 7.6 for E) showed that the both developed packaging generated a good expectation. The acceptance was similar to that reported for packaging of distinguished coffee products, such as a soluble coffee with the addition of micronized roasted coffee, with scores of 7.2 to 8.4 Santos;Benassi, 2014) and a soluble coffee enriched with antioxidants, of 7.7 to 8.2 .…”
Section: Expectation Evaluationsupporting
confidence: 82%
See 2 more Smart Citations
“…CB and IC packaging were also equally accepted (Table 2); the high average acceptance (mean value of 7.6 for E) showed that the both developed packaging generated a good expectation. The acceptance was similar to that reported for packaging of distinguished coffee products, such as a soluble coffee with the addition of micronized roasted coffee, with scores of 7.2 to 8.4 Santos;Benassi, 2014) and a soluble coffee enriched with antioxidants, of 7.7 to 8.2 .…”
Section: Expectation Evaluationsupporting
confidence: 82%
“…Although the participants did not know cold coffee beverages before the test, CB and IC beverages presented an acceptance (Table 2) within the range described for the commonly consumed hot coffee beverages, such as those produced with roasted and ground coffee -from 4.2 to 6.7 (Giacalone et al, 2019;Kalschne et al, 2019) -and soluble coffee -from 6.4 to 7.3 Santos;Benassi, 2014).…”
Section: Expectation Evaluationmentioning
confidence: 94%
See 1 more Smart Citation
“…Quanto a observação das informações nos rótulos dos alimentos, 81,2% dos participantes relataram observar o prazo de validade, seguidos de preço (58,3%) e marca (56,2%). No estudo realizado por Francisco et al (2014), os itens mais observados nos rótulos dos produtos foram validade (91%) e marca (75%).…”
Section: Questões N (%)unclassified
“…In the literature, the most used sensory tools for this beverage description in recent years are: cuptasting by a small number of experts (two or three) certified by the Specialty Coffee American Association -SCAA (ALVES et al, 2017;ISQUIERDO et al, 2012;Lópes-Gracía et al, 2016;SILVA et al, 2014), Brazil Specialty Coffee Association -BSCA (SILVEIRA et al, 2016) and in accordance to Resolution SAA-37 (PINO et al, 2017); and quantitative descriptive analysis with trained panelists (DELLA MODESTA et al, 1999;MONTEIRO, 2002;MONTEIRO et al, 2005;SANTOS et al, 2013;SILVA, 2003). On the other hand, few consumer studies have been using hedonic scale and multivariate data analysis, reporting on acceptability, emotions, perceptions and consumer behavior in different consumption contexts (FRANCISCO;OLIVEIRA, 2008;OSSANI et al, 2017). In Brazil, the Coffee Quality Program (PQC) launched in 2004 by the Brazilian Coffee Industry Association (ABIC) certifies the quality of the final beverage obtained through roasted and ground coffee, using a sensory analysis methodology validated by the ABIC, which classifies and differentiates coffees into categories.…”
Section: Introductionmentioning
confidence: 99%